2009
DOI: 10.1016/j.quascirev.2009.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Environmental history, palaeoecology and human activity at the early Neolithic forager/cultivator site at Kuahuqiao, Hangzhou, eastern China

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 115 publications
(106 reference statements)
2
62
1
1
Order By: Relevance
“…3f). Kuahuqiao lies at the boundary between the upland region to the south and west and the flat coastal plain around Hangzhou Bay to the east and north (Innes et al, 2009). This site is situated in a shallow depression between two lines of small hills, with an altitude around 4 masl.…”
Section: The Lower Yangtzementioning
confidence: 99%
See 1 more Smart Citation
“…3f). Kuahuqiao lies at the boundary between the upland region to the south and west and the flat coastal plain around Hangzhou Bay to the east and north (Innes et al, 2009). This site is situated in a shallow depression between two lines of small hills, with an altitude around 4 masl.…”
Section: The Lower Yangtzementioning
confidence: 99%
“…This site is situated in a shallow depression between two lines of small hills, with an altitude around 4 masl. Numerous studies have shown that the sea level rose rapidly on the eastern coast in the early Holocene and that the present Hangzhou bay area, including the Kuahuqiao site, was inundated (Chen and Stanley, 1998;Zong, 2004;Innes et al, 2009).…”
Section: The Lower Yangtzementioning
confidence: 99%
“…When sea level began to stabilize during the early midHolocene, it provided suitable conditions for human to move from surrounding mountainous areas onto the coast area (Chen and Stanley, 1998;Zong et al, 2007;Innes et al, 2009). They settled on the supra-tidal flat by means of collecting and fishing (Cultural Relics and Archaeology Institute of Zhejiang Province, 2003), but rice farming came to be an important food source to support the increasing population at sites.…”
Section: Paleo-ecological Implications For Rice Farming At the Hemudumentioning
confidence: 99%
“…7000e5000 cal yr BP) (Chang, 1986;Liu, 2005;Liu and Chen, 2012;Ma et al, 2016;Yao et al, 2016). These developments included the migration of early collector/foragers from hills to coastal plain (Zong et al, 2007;Innes et al, 2009), as the climate ameliorated and the sea level stabilized in the early to middle Holocene (Zong, 2004;Xu et al, 2010). Hunting and gathering were the main sources of livelihood for the mountain-based cultures in the early Holocene, while the coastal settlers were engaged in fishing and rice cultivation since the middle Holocene (Zong et al, 2007;Mao et al, 2008;Huan et al, 2014;Jiao, 2015;Qiu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the understanding of the prehistoric rice cultivation is limited by the lack of palaeoenvironmental research. Therefore, multidisciplinary studies of the palaeoecology of archaeological sites are very important for studying the origin and development of rice cultivation, and its relationship to the diet of early societies [10]. The early and later rice fields of the Hemudu culture found in the Tianluoshan site, date from 7.0 to 6.4 ka BP and 6.3 to 4.6 ka BP, respectively [11].…”
mentioning
confidence: 99%